The Comparison of Two Different Election Campaign Films in Terms of Their Approaches towards National History and Development - (:unkn) unknown (My University, 2020)
The paper is a comparative analysis of two popular mass media campaign films of Turkey and France. The 1988presidential election campaign film of French Socialist Party “La France Unie” and 2016 presidential electioncampaign film of “AK Party” the “Anka Kuşu” from Turkey have been analyzed in terms of their approaches tohistory and development. The written and visual elements of these films were analyzed by semiotics, rhetoric anddiscourse analysis methods, and their approaches to the national history and development of both parties wererevealed.

Bu çalışmada Türkiye’de ve Fransa’da popüler olan iki farklı seçim kampanyası filmi karşılaştırmalı olarak analiz edilmiştir. Fransız Sosyalist Partisi’nin 1988 yapımı “La France Unie” ve AK Parti’nin 2016 yapımı “Anka Kuşu” isimli Başkanlık Seçimi temalı filmleri bu siyasi partilerin tarihe ve kalkınmaya yönelik yaklaşımları açısından incelenmiştir. Bu filmlerin yazılı ve görsel unsurları göstergebilim, retorik ve söylem çözümleme yöntemleriyle analiz edilmiş ve her iki partinin ulusal tarihlerine ve gelişimlerine olan yaklaşımları ortaya konulmuştur.
İki Farklı Siyasal Seçim Kampanyası Filminin Gelişmeye, Kalkınmaya ve Milli Tarihe Bakışları Bakımından Karşılaştırılması
Keywords: İş; İşletme Finans; İktisat; Coğrafya; Tarih; Edebiyat; İşletme; Felsefe; Psikoloji